Outcome of cochlear implantation among prelingual children with difference age at implantation - Konting, Siti Hufaidah; Dzulkarnain, Ahmad Aidil Arafat; Rahmat, Sarah; Palanisamy, Vanitha; Abu Bakar, Zulkiflee; Narayanan, Prepageran (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2019)
Introduction: The aims of this study are to compare the outcomes of cochlear implantation (CI) among pre- lingual children at different age of implantation and to determine associated factors that affecting outcome.